2022
DOI: 10.3389/fimmu.2022.972103
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers and mechanisms of tolerance induction in food allergic patients drive new therapeutic approaches

Abstract: Immunotherapy for food-allergic patients has been effective in inducing desensitization in some populations, but long-term tolerance has remained an elusive target. A challenge facing our field is how to differentiate immune markers that are impacted by immunotherapy from those that are critical biomarkers of tolerance. Data from recent clinical trials have identified several biomarkers and mechanisms for achieving tolerance. These biomarkers include younger age, lower food-specific IgE, lower food component-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 89 publications
0
11
0
Order By: Relevance
“…There are several strengths in our study. First, the cord serum levels of antibodies could reflect directly the initial immune status of neonates [34]. Second, the incorporation of twin design could control for shared genetic and environmental confounding factors between twins, enhancing the internal validity of the study.…”
Section: Discussionmentioning
confidence: 99%
“…There are several strengths in our study. First, the cord serum levels of antibodies could reflect directly the initial immune status of neonates [34]. Second, the incorporation of twin design could control for shared genetic and environmental confounding factors between twins, enhancing the internal validity of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Concurrently, a clinical trial demonstrated that peanut OIT can decrease inflammatory cytokine production from DCs through TLR expression modulation, promoting the differentiation of regulatory T cells and inhibiting Th2 formation ( 44 ). It has also been shown that peanut OIT suppresses Th2 inflammatory responses by reducing the expression of CD40, human leukocyte antigen DR, and even CD86, but increasing CD80 expression on DCs ( 45 ).…”
Section: Mechanisms Of Oral Immunotherapy and Low-dose Oral Immunothe...mentioning
confidence: 99%
“…Antigen-specific Th2A cells (CD4 + CD45RO + CD27-CD45RBloCRTH2 + CD49d + CD161 + ) undergo a sharp decrease, especially in the first three months of OIT, followed by a gradual decline. The potential mechanisms behind this cell reduction remain unclear, although deletion, anergy, and exhaustion may all contribute ( 44 ). There was a notable decrease in the frequencies of IL-4 + , IL-9 + , and IL-10 + peanut-reactive CD4 + T cells among total CD4 + T cells in peanut-allergic individuals following OIT ( 47 ).…”
Section: Mechanisms Of Oral Immunotherapy and Low-dose Oral Immunothe...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, changes in IgG4 levels or the ratio of food sIgE/IgG4 ratio seems not related to the tolerance development. One explanation may be that IgG4 is not associated with tolerance, as it reflects previous allergen exposure and thus reflects less severe allergy at baseline [ 27 ].…”
Section: Mechanisms Of Aitmentioning
confidence: 99%